PENGOLAHAN SAMPAH ORGANIK RUMAH TANGGA MENJADI PUPUK ORGANIK DI KELURAHAN PONOROGO KOTA LUBUKLINGGAU - zico Fakhrur Rozi; Dian Samitra; Harmoko Harmoko (JURNAL CEMERLANG: Pengabdian pada Masyarakat, 2021)
Every day residents of Lubuklinggau City produce 158.2 tons of household waste. The concept of reuse, reduce, and recycle is still the best way to manage and handle waste with various existing problems. Household waste is divided into 2 parts into organic and inorganic waste. Organic waste is waste that easily decomposes such as food scraps, vegetables, dry leaves, which can still be processed and utilized. Organic waste can be processed into organic fertilizer. The methods used in this service are lectures, discussions, demonstrations and practices of processing household organic waste into organic fertilizer. This activity received a very good response from residents and the Ponorogo Village, Lubuklinggau City, because after participating in the activity, residents received information and were able to process household organic waste to be used as organic fertilizer. In addition, this activity helps the Lubuklinggau City government overcome the problem of household organic waste in Ponorogo Village, Lubuklinggau City and is expected to be a model for other families.